Pengaruh Pengetahuan Perkoperasian terhadap Minat menjadi Anggota Koperasi - Asrul; Yasnida; Gery, Mexano Hans; Oktaviani, Nichy (SAFE-Network, 2024)
This study aims to determine the influence of Location and Service on Interest in Saving at PT BPR Pembangunan Kabupaten Padang Pariaman. This study used a type of quantitative research. The samples in this study were Customers Who Save, with the sample collection method of the slovin method, namely data collected through the distribution of questionnaires and interviews to Customers totaling 80 respondents. Data analysis techniques in this study use descriptive analysis techniques, TCR analysis, validity test and reliability test, normality test, linearity test, multicollinearity test, heteroscedasticity test, multiple linear regression analysis, hypothesis test. Looking at the test results that have been carried out prove that Location has a significant effect on Saving Interest with a t-count value of t-table > of 4,970 > 1,665 and a significant rate of 0.000 < 0.05, Services do not have a significant effect on Saving Interest with a t-value of t-count > t table of 0.662 < 1.665 and a significant rate of 0.510 > 0.05, Location and Service test results have a significant effect simultaneously on Saving Interest with a value of f calculate > f The table is 17.804 > 2.72 and significant rates are 0.000 < 0.05. This shows that location and service can predict information about Interest in Saving 0.316 or 31.6%, while the remaining 0.562 or 56.2% is influenced by other factors not included in this study.